Decreased water temperature enhance Piscine orthoreovirus genotype 3 replication and severe heart pathology in experimentally infected rainbow trout - Sørensen, Juliane; Cuenca, Argelia; Olsen, Anne Berit; Skovgaard, Kerstin; Iburg, Tine Moesgaard; Olesen, Niels Jørgen; Vendramin, Niccolò (Frontiers in Veterinary Science, 2023)
PRV-3 was discovered in Denmark in 2017 in relation to disease outbreaks in rainbow trout (Oncorhynchus mykiss). While the virus appears to be widespread in farmed rainbow trout, disease outbreaks associated with detection of PRV-3 has only occurred in RAS, and has been observed during the winter. To explore possible effects of water temperature on PRV-3 infection in rainbow trout, an in vivo cohabitation trial was conducted at 5°C, 12°C, and 18°C. For each water temperature, a control tank and a tank with PRV-3 exposed fish were included. Samples were collected from all experimental groups every second week post challenge (WPC). PRV-3 load in cohabitants peaked at 6 WPC for animals at 12°C and 18°C, while it reached its peak at 12 WPC in fish at 5°C. Additionally, significantly more virus was detected at the peak in fish at 5°C compared to 12°C and 18°C. In shedders, fish at 12°C and 18°C cleared the infection considerably faster than the fish at 5°C: fish at 18°C and 12°C had cleared most of the virus at 4 and 6 WPC, respectively, high virus load persisted at 5°C until 12 WPC. Anemia was observed in the cohabitants at 12°C in correlation with the peak in viremia at 6 WPC; no changes in hematocrit level was observed at 18°C, while a non-significant reduction (due to large individual variation) trend was observed at cohabitants held at 5°C. ISG15 expression was positively correlated with PRV-3 load in all exposed groups. A distinct immune gene profile was observed in PRV-3 exposed fish maintained at 5°C compared to 12°C and 18°C. The immune markers mostly differentially expressed in the group at 5°C were important antiviral genes including RIGI, IFIT5 and RSAD2. In conclusion, these data show that low water temperature allow for significantly higher PRV-3 replication in rainbow trout, and a tendency for more severe heart pathology development in PRV-3 injected fish. Increased viral replication was mirrored by increased expression of important antiviral genes. Despite no mortality being observed in the experimental trial, the data comply with field observations of clinical disease outbreaks during winter and cold months.